The AβA2V paradigm: From molecular insights to therapeutic strategies in Alzheimer’s disease and primary tauopathies - Luisa Diomede; Andrea Conz; Michele Mosconi; Tatiana Stoilova; Matteo Paloni; Matteo Salvalaglio; Alfredo Cagnotto; Laura Colombo; Marcella Catania; Giuseppe Di Fede; Fabrizio Tagliavini; Mario Salmona (Pharmacological Research)
Alzheimer’s disease, the leading cause of dementia globally, represents an unresolved clinical challenge due to its complex pathogenesis and the absence of effective treatments. Considering the multifactorial etiology of the disease, mainly characterized by the accumulation of amyloid β plaques and neurofibrillary tangles of tau protein, we discuss the A673V mutation in the gene coding for the amyloid precursor protein, which is associated with the familial form of Alzheimer’s disease in a homozygous state. The mutation offers new insights into the molecular mechanisms of the disease, particularly regarding the contrasting roles of the A2V and A2T mutations in amyloid β peptide aggregation and toxicity. This review aims to describe relevant studies on A2V-mutated variants of the amyloid β peptide, revealing a protective effect against amyloid-β and tau pathology. Notably, special attention is given to the development of the peptide Aβ1–6A2V(D), which shows significant neuroprotective activity through inhibition of the assembly of amyloid β into amyloid fibrils. The therapeutic potential of this peptide emerges from its ability to reduce amyloid β-induced toxicity, with promising results from studies in human neuroblastoma cells and transgenic animal models.